Learning when time is an option - Randy Beavers; Richard Dadzie (Cogent Business & Management, 2020)
Generally, students would like more time in class to understand nuances of material for a variety of reasons. However, current scheduling limits terms to durations ranging from three to 16 weeks. This paper discusses an experimental system allowing learning outcomes to occur beyond normal scheduling constraints by allowing students to finish the course beyond the official allotted time and measuring the results. Data were collected from the instructor's website that posted grades with anonymous names provided by students. Univariate t-testing was used to determine any statistically significant benefits as measured by grades from the time extension. Students who had already passed the course retook exams to raise their grades, but most students who failed during the normal time constraint still failed, even with the extended time option. Passing rates decreased and overall learning outcomes measured by test scores and a homework assignment also decreased. Delivery formats were also analyzed, which vary from online only, to hybrid where the class meets once a week, to traditional where the class meets twice a week with a weekly lab. According to final grades earned, the hybrid and traditional classes performed better than online. These findings suggest that some human interaction beyond the digital classroom is necessary in order to observe improved student outcomes. A pedagogical experiment considering extended time in higher education for this length of time is not documented in the literature.
Keywords: 650; pedagogy; traditional; online; hybrid; cognitive load; introductory finance